An Approximate Auction - Jim Ingebretsen Carlson (Lund University, School of Economics and Management, Department of Economics, 2015)
This paper presents an auction procedure which is of particular interest when short execution times are of importance. It is based on a method for approximating the bidders' preferences over two types of items when complementarity between the two may exist. In particular, linear approximations of the bidders' indifference curves are made. The resulting approximated preference relation is shown to be complete and transitive at any given price vector. It is shown that an approximated Walrasian equilibrium always exists if the approximated preferences of the bidders comply with the gross substitutes condition. Said condition also ensures that the set of approximated equilibrium prices forms a complete lattice. A process is proposed which is shown to always reach the smallest approximated Walrasian price vector.
Keywords: D44; 330; Approximate auction; one-round auction; non-quasi-linear preferences; approximated preferences